Peran Pemerintah Kampung Dalam Pengelolaan Dana Kampung Kweel, Distrik Elikobel, Kabupaten Merauke - Wa Ode Sitti Mardiana; David Laiyan; ROYBERTUS OSSOR (Journal of Political and Development Issue, 2024)
ABSTRACT This study discusses the role of the Village Government in managing village funds in Kweel Village, Elikobel District, Merauke Regency, based on Permendagri Number 20 of 2018. The method used is descriptive qualitative through observation, interviews, and documentation. The results of the study indicate that the management and use of Kweel village funds are in accordance with and follow Permendagri Number 20 of 2018 and in accordance with the regulations, but there are still weaknesses in financial administration and low community participation. These are factors that hinder the Kweel village government in carrying out the development of Kweel village. lack of affirmation to the community and weak community participation so that the achievement of village goals is not optimal. To overcome these obstacles, active community involvement is needed in development planning so that it is in accordance with local needs so that the targets of development are in accordance with the wishes of the community. Keywords: Village Government, Village Funds, Management